2014
DOI: 10.1001/jamapediatrics.2013.4371
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Caffeine on Intermittent Hypoxia in Infants Born Prematurely

Abstract: clinicaltrials.gov Identifier: NCT01875159.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
89
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(93 citation statements)
references
References 39 publications
(22 reference statements)
1
89
1
1
Order By: Relevance
“…A recent study in preterm infants who had been treated with caffeine for apnea showed a decrease in the frequency of intermittent hypoxia episodes in those who received a prolonged course of therapy compared with a usual-care group. 12 Further study is necessary to determine the implications of this finding.…”
Section: Monitoring For Apnea/ Bradycardiamentioning
confidence: 97%
See 1 more Smart Citation
“…A recent study in preterm infants who had been treated with caffeine for apnea showed a decrease in the frequency of intermittent hypoxia episodes in those who received a prolonged course of therapy compared with a usual-care group. 12 Further study is necessary to determine the implications of this finding.…”
Section: Monitoring For Apnea/ Bradycardiamentioning
confidence: 97%
“…In a recent study in former preterm infants after discontinuation of medical therapy for apnea, the mean number of seconds/hour of oxygen saturation less than 80% was 20.3 at 35 weeks' PMA, decreasing to 6.8 seconds/hour at 40 weeks' PMA. 12 …”
Section: Epidemiology and Time Course To Resolutionmentioning
confidence: 99%
“…Intermittent hypoxia events were also decreased in infants for whom caffeine treatment was extended. 60 Some studies have reported a reduction in cerebral and intestinal blood flow in the first 2 hours after administration of caffeine, risk factors for the development of cerebral hemorrhage and necrotizing enterocolitis. 61 However, the trial by Schmidt et al showed no significant differences in rates of necrotizing enterocolitis and brain injuries between infants treated with caffeine and infants who received placebo.…”
Section: Unresolved Issues With Caffeinementioning
confidence: 99%
“…3,4 The potential neurodevelopmental impact of these often severe hypoxia events in the preterm infant is unknown. In one study, a greater frequency of IH in extremely low birth weight infants was associated with worse severity of retinopathy of prematurity.…”
mentioning
confidence: 99%
“…We may finally have an answer to the question of blood transfusions and reduction in apnea and IH in convalescent premature infants-it works, but the duration of the benefit remains unclear as studies have not examined the effect beyond 72 h. More importantly, does it matter? That conclusion awaits further understanding of the shortand long-term impact of IH on neurodevelopmental and other outcomes in preterm infants, and whether therapy for IH (with prolonged caffeine 4 or maintenance of higher hemoglobin thresholds) affects those outcomes. Until we have more data, Abu Jawdeh's study suggests that judicious use of red cell transfusions in premature infants 41 week of age with severe apnea or IH events may be properly considered as short-term management.…”
mentioning
confidence: 99%